A real-time LAMP-based dual-sample microfluidic chip for rapid and simultaneous detection of multiple waterborne pathogenic bacteria from coastal waters. Issue 24 (27th May 2021) - Jin, Jinglei; Duan, Lijun; Fu, Jiali; Chai, Fangchao; Zhou, Qianjin; Wang, Yaohua; Shao, Xinbin; Wang, Lei; Yan, Maocang; Su, Xiurong; Zhang, Yanjun; Pan, Junhang; et al.
Abstract : (1) A dual-sample microfluidic chip integrated LAMP method was developed to simultaneously detect 10 waterborne pathogenic bacteria within 35 min. (2) Its operations are in a highly automated format and it is suitable for on-site detection. Abstract : Waterborne pathogens are becoming a serious worldwide health hazard; thus, the regular monitoring of epidemic pathogens is urgently required for public safety. In the present study, we developed a microfluidic chip integrated loop-mediated isothermal amplification technique (on-chip LAMP) to simultaneously detect 10 waterborne pathogenic bacteria, Campylobacter jejuni, Listeria monocytogenes, Salmonella enterica, Shigella flexneri, Staphylococcus aureus, Vibrio alginolyticus, V. cholerae, V. parahemolyticus, V. vulnificus, and Yersinia enterocolitica . This method was capable of simultaneously completing 22 genetic analyses of two specimens and achieved limits of detection ranging from 7.92 × 10 −3 to 9.54 × 10 −1 pg of genomic DNA of pure bacteria per reaction. The processes from sample loading to microfluidic operation were in a highly automated format, and the LAMP reaction ran to completion within 35 minutes, with a minimal volume of 22 μl per each half of a single chip. The coefficient of variation for the time-to-positive value was less than 0.1, indicating an excellent reproducibility of the dual-sample on-chip LAMP assay. The clinical sensitivity and specificity in analyses of coastal water samples were 93.1% and 98.0%, respectively, in comparison with traditional microbiological methods. Our established dual-sample on-chip LAMP assay provides an effective multiple-pathogen analysis of waterborne bacterial pathogens. This indicates that the method is applicable for on-site detection and routine monitoring of waterborne bacteria in aquatic environments.